Endoscope-Assisted Minimally Invasive Microsurgical Removal of a Medium-Sized Acoustic Neuroma (T3a) through a Retrosigmoid Mini-Craniotomy with Preservation of Hearing - Kurucz, Peter; Barany, Laszlo; Buchfelder, Michael; Ganslandt, Oliver (Journal of Neurological Surgery Part B: Skull Base, 2019)
A 45-year-old male patient with reduced hearing in the right ear was diagnosed with a medium-sized (T3a) acoustic neuroma. The operation was performed through an individually tailored retrosigmoid mini-craniotomy. Endoscope-assisted microsurgical technique was applied to early detect the location of the facial and cochlear nerves as well as to look around the hidden corners during the surgery. The entire operation was performed without using brain retractors. The moderate intrameatal extension of the tumor and the use of angled endoscopes allowed to avoid the drilling of the internal auditory meatus. The lesion could be completely removed and the patient showed a satisfactory hearing recovery in the follow-up examinations 3 months after the surgery.The link to the video can be found at: https://youtu.be/dAYLakih924.
Keywords: acoustic neuroma; endoscope-assisted microsurgery; minimally invasive; keyhole approach; retrosigmoid craniotomy